Relationship of Angiotensinase and Vasopressinase Activities Between Hypothalamus, Heart, and Plasma in L-NAME-Treated WKY and SHR - Villarejo, A. B.; Prieto, I.; Segarra, A. B.; Banegas, I.; Wangensteen, R.; Vives, F.; de Gasparo, M.; Ramírez-Sánchez, M. (Hormone and Metabolic Research, 2014)
The renin-angiotensin system (RAS), vasopressin, and nitric oxide (NO) interact to regulate blood pressure at central and peripheral level. To improve our understanding of their interaction and their relationship with the hypothalamus and the cardiovascular system, we analyzed angiotensin- and vasopressin-metabolizing activities in hypothalamus (HT), left ventricle (LV), and plasma, collected from Wistar-Kyoto (WKY) and spontaneously hypertensive rats (SHR) treated or not with L-NAME [N(G)-nitro-l-arginine methyl ester], which inhibits the formation of NO and over-activates the sympathetic nervous system. Previous observations in WKY suggested higher formation of Ang III and Ang IV in the HT and higher availability of Ang II in plasma after L-NAME treatment. Our current results show higher formation of Ang IV and higher metabolism of vasopressin after treatment with L-NAME in the LV of WKY rats. In SHR treated with L-NAME, there is higher availability of Ang III in the HT leading to higher release of vasopressin together with lower formation of Ang 2–10. In their LV, however, there is an increase of vasopressinase. Interestingly, while the enzymatic activities in the HT and LV of WKY rats and control SHR are poorly correlated, they are well but inversely correlated in the L-NAME treated SHR. On the other hand, no significant correlations between enzymatic activities in HT or LV and plasma were noticed. Our results suggest that eNOS inhibition in SHR induces or enhances an inverse reciprocal interaction between HT and LV involving the RAS and vasopressin, which may be mediated by the autonomic nervous system.
Keywords: brain-heart connection; renin-angiotensin system; vasopressin; autonomic nervous system